{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# HW7 - Mathematics Department UCLA T Richthammer spring 09...

This preview shows pages 1–2. Sign up to view the full content.

Mathematics Department, UCLA T. Richthammer spring 09, sheet 7 May 8, 2009 Homework assignments: Math 170B Probability, Sec. 1 65. Here we will show that E ( 1 X +1 ) = 1 - (1 - p ) n +1 ( n +1) p for a binomial RV X with parameters n, p : Let X 1 , . . . , X n +1 be a Bernoulli sequence with success rate p , X ± = X 1 + . . . + X n +1 and X = X 2 + . . . + X n +1 . Calculate E ( X 1 X ± 1 { X ± > 0 } ) in the following two ways: (a) by using symmetry and P ( X ± > 0) (b) by conditioning on the value of X 1 . Answer: (a) By symmetry we have E ( X 1 X ± 1 { X ± > 0 } ) = E ( X i X ± 1 { X ± > 0 } ), which implies n +1 i =1 E ( X i X ± 1 { X ± > 0 } ) = ( n + 1) E ( X 1 1 { X ± > 0 } ). On the other hand n +1 i =1 E ( X i X ± 1 { X ± > 0 } ) = E ( X 1 + ... + X n +1 X ± )1 { X ± > 0 } ) = E ( X ± X ± 1 { X ± > 0 } ) = P ( X ± > 0) = 1 - q n +1 , and thus E ( X 1 X ± 1 { X ± > 0 } ) = 1 - q n +1 n +1 . (b) X = X ± - X 1 is a binomial RV with parameters n, p that is independent from X 1 . We have E ( X 1 X ± 1 { X ± > 0 } | X 1 = 1) = E ( 1 1+ X ) and E ( X 1 X ± 1 { X ± > 0 } | X 1 = 0) = 0, so E ( X 1 1 { X ± > 0 } ) = p E ( 1 1+ X ). Combining (a) and (b) gives the desired result. 66.* In the lecture we considered N x := min { n : X 1 + . . . + X n x } , where X 1 , X 2 , . . . are independent RVs with uniform distribution on [0 , 1]. For m ( x ) := E ( N x ) we showed m ( x ) = e x for 0 x 1 by conditioning on the value of X 1 . (a) Calculate m ( x ) for 1 x 2 by conditioning, and describe a procedure how to obtain m ( x ) for larger x . (b) Calculate m ( x ) for 0 x 1 using indicators. Answer: (a) Let x 1. By conditioning on X 1 we get. E ( N x | X 1 = x 1 ) = E ( N x - x 1 ) + 1 = m ( x - x 1 ) + 1. So m ( x ) = E ( N x ) = R 1 0 dx 1 m ( x - x 1 ) + 1. This recursive equation can be used to calculate m ( x ) for x [ n, n + 1) if you already know m ( x ) for x [ n - 1 , n ). If m n ( x ) = m ( n + x ) for x [0 , 1] we get m n ( x ) = R x 0 dx 1 m n ( x - x 1 ) + R 1 x dx 1 m n - 1 (1 + x - x 1 ) + 1 = R x 0 m n ( u ) du + R 1 x m n - 1 ( u ) du + 1. So m ± n ( x ) = m n ( x ) - m n - 1 ( x ). This gives diﬀerential equations for m n ( x ) that can be solved recursively, using the initial conditions m n (0) = m n - 1 (1) and m 0 ( x ) = e x . For instance for m 1 we get m ± 1 ( x ) = m 1 ( x ) - e x and m 1 (0) = e . Solving this diﬀerential equation by means of variation of the constant we get m 1 ( x ) = ( e - x ) e x , which gives m ( x ) = ( e - x + 1) e x - 1 for 1 x 2. (b) We have

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

### Page1 / 4

HW7 - Mathematics Department UCLA T Richthammer spring 09...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online